2021
DOI: 10.1097/qad.0000000000002976
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Fc-effector and neutralization functions in HIV-infected children define a window of opportunity for HIV vaccination

Abstract: Objectives: Antibody function has been extensively studied in HIV-infected adults but is relatively understudied in children. Emerging data suggests enhanced development of broadly neutralizing antibodies (bNAbs) in children but Fc effector functions in this group are less well defined. Here, we profiled overall antibody function in HIV-infected children. Design: Plasma samples from a cross-sectional study of 50 antiretroviral therapy-naive children (aged 1–11 years) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Moreover, we found that patients with anti‐E2 antibodies targeting Domain B and D that are known to be associated with effective neutralization 55–59 are also the ones that had antibodies strongly associated with high ADCP, further supporting the notion that there may be overlapping protective functions via dually acting antibodies. This is consistent with reports on HIV in which overlapping ADCP and neutralizing functions were observed, 24 and antibodies that maintain broad neutralization function against several HIV variants also possessed potent Fc receptor‐dependent effector functions including ADCP 14,17,24,25 . However, future studies aimed at defining the significance of ADCP in HCV, namely its role in viral clearance and clinical outcomes using live viruses, is warranted.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, we found that patients with anti‐E2 antibodies targeting Domain B and D that are known to be associated with effective neutralization 55–59 are also the ones that had antibodies strongly associated with high ADCP, further supporting the notion that there may be overlapping protective functions via dually acting antibodies. This is consistent with reports on HIV in which overlapping ADCP and neutralizing functions were observed, 24 and antibodies that maintain broad neutralization function against several HIV variants also possessed potent Fc receptor‐dependent effector functions including ADCP 14,17,24,25 . However, future studies aimed at defining the significance of ADCP in HCV, namely its role in viral clearance and clinical outcomes using live viruses, is warranted.…”
Section: Discussionsupporting
confidence: 89%
“…Among these effector functions, ADCP has been shown to correlate with immune protection against several RNA viruses, including HIV, 18 ebola, 19 dengue, 20 and influenza 21 . Importantly, in patients with HIV infection, antibodies that neutralize broader HIV variants 22,23 also possess potent Fc receptor‐dependent effector functions, including ADCP, 24,25 and antibodies that maintain broadly neutralizing function at later stages of the disease showed an early and stronger Fc‐receptor‐dependent effector function 14,17,26,27 . A positive relationship between neutralization and ADCP was also observed in patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) 15,28 and influenza virus 29 infections.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, in HIV infection, ADCC mediating antibodies have been attributed to being moderately protective in the absence of broadly neutralizing Abs 36 and are correlated with ADCC and IgG3 34 , 37 . Furthermore, high FcR responses can be enriched in pediatric HIV non-progressors 38 . Whilst vaccine antibody breadth is associated with infection-free time from SARS-CoV-2 variants 39 , similar to pre-existing antibodies pandemic and avian influenza found here.…”
Section: Discussionmentioning
confidence: 99%
“…1), and bnAbs constitute a minor component of an individual's overall HIV-1-specific antibody response [32][33][34][35][36] . Recent data suggest that in infants and children, high levels of bnAbs may develop over a shorter period of time and require fewer mutations than in adults, although the factors governing this remain unclear 37,38 .…”
mentioning
confidence: 99%